Pulsed Radiofrequency Neuromodulation of the Greater Occipital Nerve for the Treatment of Headache Disorders in Adults: A Systematic Review - Kyle De Oliveira; Nina Dhondt; Marina Englesakis; Akash Goel; Yasmine Hoydonckx (Taylor & Francis Group, 2024)
Background Pulsed radiofrequency neuromodulation (PRFN) of greater occipital nerve (GON) is considered in patients with headaches failing to achieve sustained analgesic benefit from nerve blocks with local anesthetic and steroids. However, the evidence supporting this practice is unclear.Aims This narrative systematic review aims to explore the effectiveness and safety of GON PRFN on headaches.Methods Databases were searched for studies, published up to February 1, 2024, investigating PRFN of GON for adults with headaches. Abstracts and posters were excluded. Primary outcome was change in headache intensity. Secondary outcomes included effect on monthly headache frequency (MHF), mental and physical health, mood, sleep, analgesic consumption, and side-effects. Two reviewers screened and extracted data.Results Twenty-two papers (2 randomized controlled trials (RCT), 11 cohort, and 9 case reports/series) including 608 patients were identified. Considerable heterogeneity in terms of study design, headache diagnosis, PRF target and settings, and image-guidance was noted. PRFN settings varied (38-42°C, 40-60 V, and 150-400 Ohms). Studies demonstrated PRFN to provide significant analgesia and reduction of MHF in chronic migraine (CM) from 3 to 6 months; and significant pain relief for ON from six to ten months. Mild adverse effects were reported in 3.1% of cohort. A minority of studies reported on secondary outcomes. The quality of the evidence was low.Conclusions Low-quality evidence indicates an analgesic benefit from PRFN of GON for ON and CM, but its role for other headache types needs more investigation. Optimal PRFN target and settings remain unclear. High-quality RCTs are required to further explore the role of this intervention. PROSPERO ID CRD42022363234.